The Indicators of Creditworthiness According to the (PRISM) Model and The Effectiveness of Credit Granting Decisions in Islamic Banks in Jordan - Al-Zoubi, Waleed; Al-Hatamlah, Sally; Malahim, Sari (The Arab Journal of Administration, 2023)
The study aimed to identify the indicators of creditworthiness according to the (PRISM) model, represented by (the customer’s future outlook, ability to pay, purpose of credit, guarantees, and management) and the effectiveness of credit granting decisions in Islamic banks in Jordan. to achieve this goal a questionnaire was developed and distributed The employees in the Credit Department of the Central Administration of Islamic Banks in Jordan, which are (4) banks. The number of credit employees reached (75) employees. Only (73) questionnaires were retrieved. Using the Statistical Package for Social Sciences (SPSS) program, the descriptive and inferential approach was adopted, and a number of statistical methods fit the objectives of the study, including multiple linear regression. Among the most important findings of the study, Jordanian Islamic banks apply all indicators of creditworthiness according to the (PRISM) model in their credit analysis to a high degree, and there is a statistically significant effect at the level (a≤0.05) of the indicators of creditworthiness according to the (PRISM) model on the effectiveness of credit granting decisions. The study came out with a set of recommendations. The most important of which is to enhance the degree of practice and application of creditworthiness indicators according to the (PRISM) model because of its important and strong impact on the effectiveness of credit granting decisions, by identifying training needs and intensifying development programs for managers and workers in the credit department to keep pace with all new developments and introduce them to their environment to achieve sustainable results and goals.